Thalassaemia major and infectious risk: High Mobility Group Box‐1 represents a novel diagnostic and prognostic biomarker. (8th June 2015) - Chirico, Valeria; Lacquaniti, Antonio; Piraino, Basilia; Cutrupi, Maricia; Cuppari, Caterina; Grasso, Luisa; Rigoli, Luciana; David, Antonio; Arrigo, Teresa; Salpietro, Carmelo
Summary High mobility group box ‐1 (HMGB1) represents a common causal agent for various types of diseases, including infective pathologies. This study aimed to investigate the role of HMGB1 in β‐thalassemia major (TM) by evaluating its diagnostic and prognostic role. Fifty‐one TM patients and 30 healthy subjects (HS) were enrolled. Receiver operating characteristics (ROC) analysis was employed to calculate the area under the curve (AUC) for HMGB1 to determine the best cut‐off values capable of identifying infectious episodes. Adjusted risk estimates for infective events were calculated using univariate followed by multivariate Cox proportional hazard regression analysis. Serum HMGB1 levels were higher in TM patients than in HS (14·6 ± 8·7 vs. 2·08 ± 0·9 ng/ml, P < 0·0001). Patients who underwent splenectomy were characterized by lower levels of HMGB1, when compared with patients with an intact spleen (10·2 ± 8 vs. 19·1 ± 7 ng/ml, P = 0·004). ROC analyses revealed an AUC for serum HMGB1 of 0·801, with a sensitivity and specificity of 92·3% and 68·2% to detect an infectious episode. Low HMGB1 levels predicted high risk of infective events (HR: 0·81; P = 0·006). HMGB1 represents a prognostic marker for TM patients and a predictive factor for infectious events.